Rosin-enabled ultraclean and damage-free transfer of graphene for large-area flexible organic light-emitting diodes - Zhikun Zhang (Nature Portfolio, 2017)
Ultraclean and damage-free transfer of graphene over large areas is crucial for the future development of flexible electronics and optoelectronics. Using a rosin-assisted method, the authors transfer graphene with an ultraclean surface and uniform small sheet resistance—a 4-inch monolithic organic light-emitting diode is demonstrated.